In situ remediation of lead contaminated marine sediment using bentonite, kaolin and sand as capping materials - Kabir Aliyu, Mohammed; Abd. Karim, Ahmad Tarmizi; Ming Chan, Chee; Nda, Muhammad
There is a growing public concern over the issue of sediment contamination resulting from industrial and municipal waste discharge, mining activities, and improper use of chemical fertilizer, pesticides, and wastewater irrigation. However, there is a need to reduce the continuous contamination of the water column and biota by the pollutants in the sediment. The conventional approach of contaminated sediment treatment is dredging but is expensive and requires a large area of land for disposal. In situ capping of contaminated sediment is considered as a cheaper technique compared to dredging and efficient treatment technology to immobilize pollutants in sediments on site. A laboratory-scale capping experiment was conducted to evaluate the effectiveness of using bentonite (B), kaolin (K), a mixture of bentonite with kaolin (BK), and sand in immobilizing lead-contaminated sediment using in situ capping treatment technology. The results indicated that applying bentonite, kaolin, and sand as capping materials has the potential to effectively reduce the release of lead from the heavily spiked contaminated marine sediment (3000 ppm) to the overlying water. The adsorption kinetics results obtained showed that the experimental data for adsorption of Pb fitted well to the Elovich, Second-order and Twoconstant rate kinetic models as judged by highest values of R2 and the lowest values of standard error of estimate (SE) such as R2 of 0.937, 0.735, 0.932 with SE values of 0.23, 2.62 and 0.26 for B, K and BK respectively in the Elovich, likewise R2 of 0.817, 0.935, 0.821 with SE values 0.33, 0.07 and 0.19 for B, K and BK in the Second-order and R2 of 0.938, 0.637, 0.925 with SE values of 0.000135, 0.0015 and 0.00024 for B, K and BK were obtained for Two-constant rate models, which implied that the process of adsorption was by chemisorption.